Stranger child abduction and guardianship: Accompaniment and surveillance in attempted and completed cases. Issue 4 (November 2016) - Collie, Craig; Shalev Greene, Karen
Abstract The Routine Activity Theory construct of capable guardianship is used to examine the features of 78 cases of stranger child abduction, using an outcome-based approach to establishing the effectiveness of various potential sources of guardianship in preventing abduction attempts from becoming completed, and to test widely held and taught beliefs on this subject. Results show only direct oversight provided by an adult who sees themselves as personally responsible for a child to be a very effective means of abduction prevention, both dissuading and disrupting offences. Guardianship provided by other actors, such as peers and third-party passers-by, were not effective. Accompaniment by other children could dissuade offending, but failed to disrupt offences in progress. Sources of natural surveillance were ineffective. The finding regarding the ineffectiveness of peers was particularly surprising. The theoretical and practical implications of these findings are discussed.